KAJIAN KERUSAKAN MATERIAL SUPERHEATER TUBE 2” DENGAN PENDEKATAN STANDAR ASTM - Koos Sardjono Kuntadi (Badan Standardisasi Nasional, 2006)
Equipments used in industry process and migas is generally designed from alloy of steel which hold up to high temperature and attack corrosion. Based on that, it’s require to be conducted an material operation and election, like a component Boiler that is Secondary Superheater is generally weared by pipe from alloy of steel material Cr- Mo or steel with Austenitik type.To know the damage of Secondary Superheater tube 2